DNA–protein crosslinks from environmental exposure: Mechanisms of formation and repair. (9th July 2020) - Kojima, Yusuke; Machida, Yuichi J.
Abstract: Many environmental carcinogens cause DNA damage, which can result in mutations and other alterations in genomic DNA if not repaired promptly. Because of the bulkiness of the lesions, DNA–protein crosslinks (DPCs) are one of the types of toxic DNA damage with potentially deleterious consequences. Despite the importance of DPCs, how cells remove these complex DNA adducts has been incompletely understood. However, major progress in the DPC repair field over the past 5 years now supports the view that cells are equipped with multiple mechanisms to cope with DPCs. Here, we first provide an overview of environmental substances that induce DPCs, describing the sources of exposure and mechanisms of DPC formation. We then review current models of DPC repair and discuss their significance for environmental carcinogens.